Perception on the usage of tablet among students in Malaysian universities as their learning tool / Nur Adriana Adrina Shahrani ... [et al.] - Shahrani, Nur Adriana Adrina; Rasli, Izzah Irdina; Zainol Abidin, Muaz; Ariffin, Muhammad Afiq; Abdul Rani, Nur Shazana (Faculty of Communication & Media Studies, 2023)
Technological development has reformed our way of living tremendously from every aspect, including education. The availability and use of digital tools such as tablet computers in early year education has increased significantly in recent years. This study is to investigate perception on the usage of tablet computer among students in Malaysian universities as their learning tool. The final sample of students (n=103) participated in the survey representing 34.3% of the expected sample population. From the data analysed, almost 99% know tablet's existence and 91.3% had use tablet before. Technology also enables better practise, resource sharing, and communication for these roles so that everyone in the system is committed to working together to promote student learning. The use of technology to support learning has never been more possible or advanced. To enhance the results, the study should include more respondents from various higher education contexts in order to reach a larger part of the population.